Islamic Boarding School Economic Business Models in Improving Teacher Welfare in Deli Serdang - Marni, Dina; Yafiz, Muhammad; Kamal Rokan, Musthapa (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The purpose of this research is to find out the economic business model of Islamic boarding schools in Deli Serdang Regency, to analyze the role of Islamic boarding school economic businesses in improving the welfare of Islamic boarding school teaching staff in Deli Serdang Regency, and to analyze the supporting and inhibiting factors of Islamic boarding school economics in improving the welfare of Islamic boarding school teaching staff in Deli Serdang Regency. The research approach is qualitative research. The location of this research is in Deli Serdang Regency, North Sumatra province. Researchers visited 4 Islamic boarding schools in Deli Serdang and determined 4 Islamic boarding schools that had the highest number of students or female students. The stages carried out by researchers in data analysis are as follows: Gathering information, selecting and reducing data, presenting data, and drawing conclusions and suggestions. Islamic boarding schools’ economic business capital consists of two types, some capital comes from Islamic boarding schools and some comes from the shares of employees and teachers under the auspices of cooperatives, so the management is divided into two, namely: businesses managed by Islamic boarding schools and businesses managed by employee and teacher cooperatives. For businesses managed by Islamic boarding schools, especially at Islamic boarding schools, teachers are given access to deposit merchandise at Islamic boarding schools. For every business that is managed by the cooperative, members and teachers who own shares will get profit sharing every year. Businesses managed by cooperatives are supported by facilities from Islamic boarding schools so profits are also shared between Islamic boarding schools or foundations. Keywords: Business Model, Islamic Boarding School Economics, Teacher Welfare The purpose of this research is to find out the economic business model of Islamic boarding schools in Deli Serdang Regency, to analyze the role of Islamic boarding school economic businesses in improving the welfare of Islamic boarding school teaching staff in Deli Serdang Regency, and to analyze the supporting and inhibiting factors of Islamic boarding school economics in improving the welfare of Islamic boarding school teaching staff in Deli Serdang Regency. The research approach is qualitative research. The location of this research is in Deli Serdang Regency, North Sumatra province. Researchers visited 4 Islamic boarding schools in Deli Serdang and determined 4 Islamic boarding schools that had the highest number of students or female students. The stages carried out by researchers in data analysis are as follows: Gathering information, selecting and reducing data, presenting data, and drawing conclusions and suggestions. Islamic boarding schools’ economic business capital consists of two types, some capital comes from Islamic boarding schools and some comes from the shares of employees and teachers under the auspices of cooperatives, so the management is divided into two, namely: businesses managed by Islamic boarding schools and businesses managed by employee and teacher cooperatives. For businesses managed by Islamic boarding schools, especially at Islamic boarding schools, teachers are given access to deposit merchandise at Islamic boarding schools. For every business that is managed by the cooperative, members and teachers who own shares will get profit sharing every year. Businesses managed by cooperatives are supported by facilities from Islamic boarding schools so profits are also shared between Islamic boarding schools or foundations.